EFFECTIVENESS OF HIBISCUS SABDARIFFA ON BLOOD PRESSURE OF HYPERTENSION PATIENTS - Harmili, Harmili; Fadlilah, Siti; Sucipto, Adi (Jurnal Keperawatan Respati Yogyakarta, 2021)
To prevent the dangers of hypertension, it is necessary to maintain blood pressure. Natural ingredients for non-pharmacological hypertension therapy are rosella flowers. Rosella (Hibiscus sabdariffa) contains flavonoids, as a diuretic, lowers blood pressure, lowers blood viscosity and stimulates bowel movements. The anthocyanins contained in rosella have an antihypertensive effect. This study aims to determine the effect of rosella flowers on blood pressure in hypertensive patients. This type of research is a quasy experiment with a Pre Test and Post Test Nonequivalent Control Group. The sample was 18 people in the control group and 17 people in the intervention group. The intervention sample was given a decoction of 2 gr roselle petals every day for seven days. The research instrument used a digital sphygmomanometer, observation sheets, and Standard Operating Procedures. Statistical test using Paired T Test. The control group had an increase in systolic and diastolic mean of 6.3 mmHg and 2.0 mmHg. In the roselle flower group, there was a decrease in the systolic and diastolic mean of 12.64 mmHg and 11.58 mmHg. The difference between the changes in the mean posttest-prettest systolic and diastolic control and roselle groups was 18.94 mmHg and 13.58 mmHg. The bivariate results of the systolic and diastolic pretest-posttest in the roselle flower group obtained p-values ​​of 0,000 and 0,000. Comparison of systolic and diastolic blood pressure in the control group and rosella flowers obtained p-values ​​of 0.000 and 0.000. Rosella flower is effective in reducing systolic and diastolic blood pressure in hypertensive patients. Keywords: Blood Pressure; Hibiscus Sabdariffa; Hypertension